IMF Survey : Volume 28, Issue 15. (IMF Survey; IMF Survey, 1999)
In a press release issued on July 28, the IMF announced it has approved a 17-month Stand-By credit for Russia equivalent to SDR 3.3 billion (about USD 4.5 billion) to support the government's 1999-2000 economic program. There will be seven equal disbursements of SDR 471.4 million (about USD 640 million), with the first installment to be released immediately. Subsequent installments will depend on quarterly reviews being completed and performance criteria and structural benchmarks beingmet. At the conclusion of the IMF Executive Board meeting, IMF First Deputy Managing Director Stanley Fischer made the following statement.